Patung Pantak Panyugu : Manifestasi Sistem Nilai dan Budaya Kognitif pada Kepercayaan Suku Dayak Kanayatn - Cindy, Cindy; Musa, Dahniar Th.; Efriani, Efriani (Sosial Budaya, 2023)
This paper has aimed to describe the history of the founding of Panyugu Tiansa', the process of making the Panyugu statue and analyze the symbol and meaning of the Panyugu statue as a culture in the form of values and cognitive systems in the Kanayatn Dayak ethnicity. This study used ethnographic research with qualitative research methods. The theory used to analyze the object of this research uses the symbolic interpretative theory of Clifford Geertz, namely the model of and model for. The results of this study indicate that Panyugu Tiansa', where the Pantak Panyugu statue is placed, has existed for 150 years. Panyugu is still visited by the people and has been passed down for four generations. The process of making a Pantak statue is carried out by carrying out various rituals such as at the beginning of manufacture a traditional Ngalantekant ritual is carried out which aims to ask for permission, then in the process of planting the Pantak statue a certain traditional ritual is carried out which is also carried out with several materials that need to be prepared such as pork, chicken, tumpi, singkatek and so on. Pantak Arca as a Knowledge System (Model Of) Pantak Arca as a medium for ancestral dwellings. The Pantak Panyugu statue was made by the community as a form of respect for their ancestors who contributed to agriculture, so that the Pantak Panyugu statue plays a role in the process of community agricultural traditions, especially the Ka' Panyugu tradition. The Pantak Panyugu statue is a value system (Model For) which guides that the Pantak Panyugu statue is a place for humans to ask for sustenance, ask for protection, ask for help and so on, especially in agriculture.